Emeritus Professor Dr. Ian Hector Frazer, the Pioneer of HPV Vaccine against Cervical Cancer in Women: A Bio-Bibliographic Assessment - Koley, Susanta (Information Research Communications, 2025)
Aim This paper aims to provide an assessment of cervical cancer research related to Human Papillomavirus (HPV) infections, with a particular focus on the scientific contributions of Dr. Ian Hector Frazer, a Scottish-born Australian immunologist. He is best known for co-developing the HPV vaccine, a major breakthrough in cervical cancer prevention. This study encompasses an analysis of 573 publications from 1997 to 2024, applying bibliometric techniques to quantitatively assess Dr. Frazer’s scholarly output, presenting a comprehensive portrait of his impact on the field. Background Historical records of cervical cancer trace back to 400 BCE, when it was considered an untreatable illness. Over time, extensive research led to the discovery of its viral cause “Human Papillomavirus (HPV)” and eventually to the development of a preventive vaccine. A major breakthrough came in 2006 with the introduction of the HPV vaccine, which significantly reduced the risk of cervical cancer in women. This landmark achievement is credited to Dr. Ian Frazer, whose ground-breaking work marked a turning point in the fight against cervical cancer, widely recognized as a pioneering figure of the 21st century for his invention of the HPV vaccine. Methodology The data of Dr. Frazer’s 573 publications were primarily harvested from Google Scholar (GS) and Dr. Frazer’s institutional profile at the Frazer Institute, The University of Queensland, Australia. Attention was given on selection of various bibliographical elements from all publications. After careful filtration and validation, the publication data were compiled and organized using Microsoft Excel and Word to facilitate tabulation and further analysis. Standard bibliometric techniques of different informetric indicators were employed to conduct a comprehensive scientometric assessment, culminating in the creation of a medicometric profile of Dr. Frazer’s scholarly contributions to medical science. Findings Dr. Ian Frazer has authored a total of 573 publications over a span of 48 years in cancer research. Among these, 76 are single-authored works, while 496 are collaborative publications. The majority of his contributions are journal articles and the highest number of his papers i.e. 26 in total has appeared in the journal Virology. His first publication appeared in 1977, at the age of 24, and his most productive period occurred between 2002 and 2006 with 100 papers. His most frequent collaborator is G.J. Leggatt, with whom he co-authored 76 papers. The median age of his research productivity is 30, and his Productivity Coefficient is calculated at 0.63, indicating a high level of consistent output, averaging nearly 12 publications per year. His most cited work, published in 1997, has received 1,325 citations according to the Scopus database. Additional interfaces have been derived from this bibliometric investigation. Conclusion Although numerous bio-bibliometric studies have been conducted in the domain of bibliometric research, no comprehensive analysis has yet been undertaken on the scientific contributions of Dr. Ian Frazer, an eminent medical scientist. This study, therefore, represents an original and significant effort that offers valuable insights for cancer researchers, medical historians, educators, students, librarians, information scientists, biographers, and other knowledge seekers interested in the development of cancer immunology and vaccine research.
Keywords: Ian Hector Frazer; Ian Frazer; Human Papillomavirus (HPV); Cervical Cancer; Cervix Uteri; Female Cancer; Cancer Research; Immunologist; Bio-Bibliometric Study; Bibliometric; Informatics; Citation Growth Rate; Relative Growth Rate; Doubling Time; Fifty-Percentile Age; Collaboration Coefficient (CC); Collaboration Index (CI); Modified Collaboration Coefficient (MCC)